2018
DOI: 10.1200/jco.2017.76.4696
|View full text |Cite|
|
Sign up to set email alerts
|

Neurocognitive Outcomes and Interventions in Long-Term Survivors of Childhood Cancer

Abstract: Recent research has demonstrated that survivors of childhood cancer are at risk for a myriad of late effects that affect physical and mental quality of life. We discuss the patterns and prevalence of neurocognitive problems commonly experienced by survivors of CNS tumors and acute lymphoblastic leukemia, the two most commonly researched cancer diagnoses. Research documenting the direct effects of tumor location and treatment type and intensity is presented, and patient characteristics that moderate outcomes (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
198
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 213 publications
(220 citation statements)
references
References 106 publications
11
198
1
Order By: Relevance
“…Central nervous system (CNS) cancers are the most frequently occurring solid tumors in children and most common cause of cancer deaths among children 0 to 14 years of age . Despite improvements in survival, morbidity remains high . Sleep disturbances are frequently reported during treatment and survivorship .…”
Section: Introductionmentioning
confidence: 99%
“…Central nervous system (CNS) cancers are the most frequently occurring solid tumors in children and most common cause of cancer deaths among children 0 to 14 years of age . Despite improvements in survival, morbidity remains high . Sleep disturbances are frequently reported during treatment and survivorship .…”
Section: Introductionmentioning
confidence: 99%
“…The pediatric oncologist plays an important role in assuring optimal outcomes for the children they treat, including outcomes associated with neurocognitive function. A number of CNS‐directed treatments are both necessary and unavoidable to ensure the improving survival rates of many pediatric cancers . Supporting and educating families about neurocognitive impacts of therapy is an important component of childhood cancer care .…”
Section: Introductionmentioning
confidence: 99%
“…A number of CNS-directed treatments are both necessary and unavoidable to ensure the improving survival rates of many pediatric cancers. 10 Supporting and educating families about neurocognitive impacts of therapy is an important component of childhood cancer care. 11 However, a recent study reported that approximately half of parents do not recall receiving information about cognitive impacts from their oncology treatment team and nearly half felt unprepared for their child's return to school.…”
Section: Introductionmentioning
confidence: 99%
“…With advances in treatment options, overall survival for pediatric brain tumors has significantly improved and the majority of patients become long-term survivors (Gajjar et al, 1997;Merchant et al, 2009;Packer et al, 2006). The presence of a Central Nervous System tumor increases the risk of cognitive impairment, with 20-50% of patients exhibiting such impairment at the time of diagnosis (Krull et al, 2018). In addition to experiencing cognitive deficits from the presence of the tumor, survivors of childhood brain tumors can develop sequelae from their diagnosis and from tumor directed therapies, such as surgery, chemotherapy, and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%